2022
DOI: 10.3390/su14084668
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Frequency Ratio and Analytic Hierarchy Process for Forest Fire Susceptibility Mapping in the Western Region of Syria

Abstract: Forest fires are among the most major causes of global ecosystem degradation. The integration of spatial information from various sources using statistical analyses in the GIS environment is an original tool in managing the spread of forest fires, which is one of the most significant natural hazards in the western region of Syria. Moreover, the western region of Syria is characterized by a significant lack of data to assess forest fire susceptibility as one of the most significant consequences of the current w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…5). The spatial distributions of C factor values showed that the southern and western regions showed high values due to the pressure of human activity, particularly urban sprawl, dense agriculture and forest fire (Abdo et al, 2022). Meanwhile, low values of factor C are concentrated in the northern and eastern regions due to the density of vegetation and grass cover, which enhances the biological protection of the soil profile.…”
Section: Resultsmentioning
confidence: 99%
“…5). The spatial distributions of C factor values showed that the southern and western regions showed high values due to the pressure of human activity, particularly urban sprawl, dense agriculture and forest fire (Abdo et al, 2022). Meanwhile, low values of factor C are concentrated in the northern and eastern regions due to the density of vegetation and grass cover, which enhances the biological protection of the soil profile.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the vital role of fire in the renovation and growth of plants (Durigan and Ratter 2016;Abdo 2018;Abdo et al 2022), however, most of the wildfires originating over the biome arise from human actions (Mataveli et al 2018;Silva Junior et al 2019). Concern exists regarding Cerrado's ability to support endemic fauna and flora (Durigan and Ratter 2016;Garcia and Ballester 2016;Abreu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The collapse of the economy and infrastructure has proliferated informal, unregulated industries such as petroleum refining and electroplating industries, tanneries, use of poor-quality agricultural fertilizers and the burning of leaded fossil fuels and coal (UN-Habitat, 2022). These indirect impacts of the devastating conflict exacerbate the direct environmental impacts of munitions, shelling, and military manoeuvres (Zwijnenburg et al, 2020) and are set against long-term regional drought, placing severe pressure on water resources and increasing the incidence of forest fires (Homsi et al, 2020;Abdo et al, 2022). In combination, these factors create an extraordinary level of threat to soil quality, human health and the agricultural economy, both as direct hazards and longer-term risks to socio-environmental recovery and restoration in a region where agriculture is historically the primary source of income and is now a principal factor in food security (UNOCHA, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…4 These indirect impacts of the devastating conict exacerbate the direct environmental impacts of munitions, shelling, and military manoeuvres 5 and are set against long-term regional drought, placing severe pressure on water resources and increasing the incidence of forest res. 6,7 In combination, these factors create an extraordinary level of threat to soil quality, human health and the agricultural economy, both as direct hazards and longer-term risks to socio-environmental recovery and restoration in a region where agriculture is historically the primary source of income and is now a principal factor in food security. 8 The elements Pb, As, Hg, Cd, Co, Zn, Ba, Cu, Cr, Ni, Pd, Sn, V, and Pt are a group of metals and metalloids that have a relatively high density and are toxic even at parts per million (ppm) levels.…”
Section: Introductionmentioning
confidence: 99%